2013
DOI: 10.1161/circresaha.113.300218
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Paradigms in Cardiomyopathies Associated With Cancer Therapies

Abstract: The cardiovascular care of cancer patients (“Cardio-Oncology”) has emerged as a new discipline in clinical medicine given recent advances in cancer therapy, and is driven by the cardiovascular complications that occur as a direct result of cancer therapy. Traditional therapies, such as anthracyclines and radiation, have been recognized for years to have cardiovascular complications. Less expected were the cardiovascular effects of “targeted” cancer therapies, which were initially felt to be specific to cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
127
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 92 publications
1
127
0
1
Order By: Relevance
“…These studies further suggest that the chronic manifestations of DOXinduced cardiotoxicity may result from myocardial injuries associated with acute DOX exposure [18]. Thus far multiple mechanisms of DOX-induced cardiotoxicity have been proposed in the literature [19][20][21][22][23][24][25][26]. Among the proposed mechanisms, DOXinduced generation of reactive oxygen species (ROS) is the central mediator of numerous direct and indirect cardiac adverse consequences.…”
Section: Doxorubicin-induced Cardiotoxicitymentioning
confidence: 99%
“…These studies further suggest that the chronic manifestations of DOXinduced cardiotoxicity may result from myocardial injuries associated with acute DOX exposure [18]. Thus far multiple mechanisms of DOX-induced cardiotoxicity have been proposed in the literature [19][20][21][22][23][24][25][26]. Among the proposed mechanisms, DOXinduced generation of reactive oxygen species (ROS) is the central mediator of numerous direct and indirect cardiac adverse consequences.…”
Section: Doxorubicin-induced Cardiotoxicitymentioning
confidence: 99%
“…The redox environment of the cell is extremely important to control either apoptosis or autophagy. One of the most widely cited and accepted mechanisms underlying cardiotoxicity involves the formation of ROS, leading to oxidative stress [31][32][33][34]. A previous study reported that ROS and nitric oxide (NO) generation was induced by evodiamine time-dependently in human cervical carcinoma HeLa cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…ErbB2 is a transmembrane glycoprotein receptor which plays a key role in cell growth, including myocyte growth, and inhibition of apoptosis [7][8][9]42]. Cardiac endothelial cells produce the growth factor NRG1, which activates the Her-2/Her-4 complex, thus triggering cascades of ERK-MAPK and PI3K-Akt signaling pathways, promoting cell survival [43].…”
Section: Vascular Damage Induced By Inhibition Of Other Kinases Than mentioning
confidence: 99%
“…Such molecules are characterized by a targeted action [1] on well-known proteins with important roles in cancer biology [2]. However, despite their selective action, they can still cause cardiovascular complications such as arterial hypertension, QT interval prolongation, heart failure (HF), cardiomyopathy, stroke, acute myocardial infarction (AMI), thromboembolic events and cardiovascular deaths [3,4] since the same targets also play a role in maintaining cardiovascular homeostasis [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%